Integrating environmental physiotherapy into New Zealand undergraduate education: exploring current practice - Stone, Olivia M. L.; Bryant, Katrina; Hale, Leigh (Frontiers in Public Health, 2024)
This paper describes the integration of environmental physiotherapy education into the physiotherapy curriculum in a New Zealand university in response to the environmental physiotherapy agenda and the University of Otago Sustainability Framework. We describe and discuss three learning activities, the associated challenges and lessons learnt, and the current position. Given the encompassing nature of environmental and health interactions, we aimed for multilayer immersive experiences using a range of pedagogical approaches. The first learning activity example exemplifies embracing and threading Aotearoa New Zealand’s indigenous knowledge and practices throughout our BPhty curriculum. The second example demonstrates how environmental physiotherapy can be made explicit within a delineated learning activity. In the third example, we describe a clinical placement learning activity that occurred in our student-led private practice. Recent full accreditation of the curriculum by the New Zealand Registration Board and positive student evaluations and feedback demonstrate that this integrated holistic curriculum is both acceptable and enjoyable. Frequent and rapid curriculum modifications in response to the COVID19 Global pandemic’s impact on teaching and learning have however prevented full formal curriculum evaluation at this stage. We envisage that this educational approach be an ongoing process of review and restructure. Aligned with global trends toward sustainability in healthcare, our goal is to prepare students to address the growing environmental influences on public health. By integrating environmental physiotherapy philosophy into the undergraduate physiotherapy curriculum, we aim to develop holistic healthcare perspectives in students that will strengthen future physiotherapy practice in New Zealand and internationally.